2020
DOI: 10.1017/s1368980020001329
|View full text |Cite
|
Sign up to set email alerts
|

Home gardening and associations with fruit and vegetable intake and BMI

Abstract: Abstract Objective: To understand who engages in home gardening and whether gardening is associated with fruit and vegetable intake and weight status. Design: A national cross-sectional survey. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…This study suggests that access to a HCG has a positive relationship with vegetable intake, a significant contributor to adolescent and adult health. 14,26 Results indicated that students ate more vegetables on average than fruit and ate significantly more vegetables with access to a HCG while having a higher self-perception of health. Adolescent fruit and vegetable access and consumption should continue to be examined and evaluated as a potential tool for changing nutrition-related behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that access to a HCG has a positive relationship with vegetable intake, a significant contributor to adolescent and adult health. 14,26 Results indicated that students ate more vegetables on average than fruit and ate significantly more vegetables with access to a HCG while having a higher self-perception of health. Adolescent fruit and vegetable access and consumption should continue to be examined and evaluated as a potential tool for changing nutrition-related behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggests the potential of concerns about biodiversity loss for also motivating diet changes, because this topic has received much less attention. However, several studies show significant correlations between adult gardening (home gardening or participation in urban gardening) and higher intakes of fruits and vegetables and, to a lesser extent, reducing intakes of processed foods and meat, although the research does not allow causal interpretations (Freeman et al, 2012;Garcia, Ribeiro, Germani, & Bógus, 2018;Beavers, Atkinson, & Alaimo, 2020;Kegler et al, 2020).…”
Section: Environmental Motives For Pro-environmental Food Choicesmentioning
confidence: 99%
“…BMI and WC are easily obtainable and have proved to be strong predictors of metabolic syndrome, type 2 diabetes, and cardiovascular disease in adults and children [ 42 ]. Many scholars of the United States and other developed countries have used SGA to explore its impact on children’s BMI and other anthropometric outcomes [ 43 , 44 , 45 ]. Therefore, we systematically reviewed and meta-analyzed the effects of SGA on anthropometric outcomes of school-age children (7–12 years old), gathering experimental information on BMI and WC changes in SGA and other interventions.…”
Section: Introductionmentioning
confidence: 99%